2022
DOI: 10.3389/fmed.2022.913866
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Organs Uptake on Baseline 18F-FDG PET/CT as an Alternative to Total Metabolic Tumor Volume to Predict Event-Free Survival in Classical Hodgkin's Lymphoma

Abstract: PurposeHealthy organs uptake, including cerebellar and liver SUVs have been reported to be inversely correlated to total metabolic tumor volume (TMTV), a controversial predictor of event-free survival (EFS) in classical Hodgkin's Lymphoma (cHL). The objective of this study was to estimate TMTV by using healthy organs SUV measurements and assess the performance of this new index (UF, Uptake Formula) to predict EFS in cHL.MethodsPatients with cHL were retrospectively included. SUV values and TMTV derived from ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
2
6
1
Order By: Relevance
“…24 Regarding TMTV, this PET feature was confirmed in our study as prognostic factor for PFS in the univariate analysis, which is consistent with almost all studies assessing baseline TMTV as risk factor in HL, [10][11][12][14][15][16][17][18] especially the recent studies including patients treated with escalated BEACOPP. 13,19,20 The presence of a bulky tumor was not a predictor of a poor outcome in our study, confirming that quantifying the volume rather than the single largest diameter of the mass gives a more relevant prognosis information. However, the cutoff value of TMTV parameter discriminating high-and low-risk groups in our study differs from that described in the 3 other studies, including also early and advanced HL patients (107 cm 3 vs 33 cm 310 vs 225 cm 316 vs 271 cm 3 ).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…24 Regarding TMTV, this PET feature was confirmed in our study as prognostic factor for PFS in the univariate analysis, which is consistent with almost all studies assessing baseline TMTV as risk factor in HL, [10][11][12][14][15][16][17][18] especially the recent studies including patients treated with escalated BEACOPP. 13,19,20 The presence of a bulky tumor was not a predictor of a poor outcome in our study, confirming that quantifying the volume rather than the single largest diameter of the mass gives a more relevant prognosis information. However, the cutoff value of TMTV parameter discriminating high-and low-risk groups in our study differs from that described in the 3 other studies, including also early and advanced HL patients (107 cm 3 vs 33 cm 310 vs 225 cm 316 vs 271 cm 3 ).…”
Section: Discussionsupporting
confidence: 73%
“…However, the cutoff value of TMTV parameter discriminating high-and low-risk groups in our study differs from that described in the 3 other studies, including also early and advanced HL patients (107 cm 3 vs 33 cm 310 vs 225 cm 316 vs 271 cm 3 ). 19 However, we applied the same segmentation method (tumor delineation threshold set at 41% of the SUV max ) and the same feature dichotomization method (based on ROC curve) as performed in the other studies. The few observed events and the small size of the study population reported in the different studies might be the explanation to this discordancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations